Redesign do calçado com solado de corda a partir dos resíduos têxteis da indústria do vestuário: inovação de material e avaliação de conforto - Santos, Heliana Marcia [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The garment production generates a high volume of textile waste that can be reused to generate new impacts due to this activity, new proposals for reuse and increading the life cycle of this material are required. In this context, the role of design is critical in the development of creative solutions for these problems. This master dissertation aims to develop footwear from textile waste and analyze the performance of the new product in comparison the Alpargata Rueda. For this, thirty female adult volunteers took part in the experiment; Their shoes size were 36 to 39 (Brazilian standard). The procedures included the use of both shoes in randomized order and latter fulfillment of evaluating questionnaires which include three aspects; aesthetic, ergonomic and and quality of use. In order to carry on a post-use assessment of espadrilles Rueda and esquadrilles of textile waste, we employed shoes in sizes 36-37 and 38-39 (Brazilian Standard). The volunteers wore the two pair of shoes, randomly, during about five minutes, simulating the processes carried out in shoe stores when buying shoes. For the evaluation of footwear data was collected via a discomfort / comfort subjective protocol after use with a Likert Scale. The analysis method included descriptive statistics and the Wilcoxon test for independent variables, applied for comparison of samples (p > 0.05). The results were satisfactory pointing out that the espadrille of textile waste produced better results in all aspects evaluated and the results were significant for the Wilcoxon test in comparison with espadrilles Rueda

A produção do vestuário gera um elevado volume de resíduos têxteis que podem ser reaproveitados para a geração de novos produtos. Considerando a quantidade de resíduos têxteis descartados e os consequentes impactos ambientais são necessárias propostas de reutilização e aumento do ciclo de visão deste material. Neste contexto, é fundamental o papel do design no desenvolvimento de soluções criativas para esses problemas. Esta dissertação teve como finalidade desenvolver um calçado de resíduos têxteis e analisar o desempenho comparado do produto desenvolvido em relação à Alpargata Rueda. Para tantos, participaram da avaliação dos calçados 30 voluntários do gênero feminino com idade acima de 18 anos, que usassem calçados com a numeração 36 até 39 para fazer uma avaliação pós-uso da Alpargata de Rueda e alpargata de resíduos têxteis nos tamanhos 36-37 e 38-39. As voluntárias vestiram os dois calçados, aleatoriamente, permanecendo com cada modelo por volta de dois a cinco minutos, e simulando os processos realizados em lojas de calçados no momento da compra de calçado. Para a avaliação do calçado foram coletados dados através de um protocolo de desconforto percebido após o uso. O método de tratamento dos dados utilizado foi estatística descrita e o teste de Wilcoxon (p> 0,05) para variáveis independentes, empregado para comparação das amostras. Os resultados foram satisfatórios e apontaram que a alpargata de resíduos têxteis, quando utilizada pelos sujeitos entrevistados, apresentou melhores resultados nos aspectos avaliados e os resultados foram significativos para o teste de Wilcoxon em comparação com a Alpargata Rueda
Keywords: Desenho industrial; Engenharia humana; Resíduos; Tecidos; Calçados; Industrial design